2000
DOI: 10.1038/sj.onc.1203592
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic crosstalk between the endoplasmic reticulum and mitochondria controlled by Bcl-2

Abstract: Apoptosis involves mitochondrial steps such as the release of the apoptogenic factor cytochrome c which are e ectively blocked by Bcl-2. Although Bcl-2 may have a direct action on the mitochondrial membrane, it also resides and functions on the endoplasmic reticulum (ER), and there is increasing evidence for a role of the ER in apoptosis regulation as well. Here we uncover a hitherto unrecognized, apoptotic crosstalk between the ER and mitochondria that is controlled by Bcl-2. After triggering massive ER dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
191
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(202 citation statements)
references
References 57 publications
10
191
1
Order By: Relevance
“…To elicit robust cell death in response to ER stress, BFA-treated cells were coincubated with CHX so as to limit the activation of ATF6 and IRE1 translation-dependent survival pathways, as was done previously. 8 We reported that ER stress-induced apoptosis was not prevented by caspase inhibition with Z-VAD.fmk but could be blocked by Pefabloc, a general inhibitor of serine protease activity. 11 We therefore sought to identify the serine protease(s) responsible for cell death observed in our system.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…To elicit robust cell death in response to ER stress, BFA-treated cells were coincubated with CHX so as to limit the activation of ATF6 and IRE1 translation-dependent survival pathways, as was done previously. 8 We reported that ER stress-induced apoptosis was not prevented by caspase inhibition with Z-VAD.fmk but could be blocked by Pefabloc, a general inhibitor of serine protease activity. 11 We therefore sought to identify the serine protease(s) responsible for cell death observed in our system.…”
Section: Resultsmentioning
confidence: 94%
“…CHOP/GADD153, the pro-apoptotic translational-dependent mediator of ER stress-induced cell death, 17 is not a player in our model system because we co-treated cells with CHX so as to bypass the expression of protective UPR genes, as was done previously. 8,11 Therefore, we have defined an ER stressinduced cell death pathway that is independent of CHOP/ GADD153. We also excluded calpains from playing a role in this paradigm because none of the calpain inhibitors tested had any protective effect on ER stress-induced apoptosis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were transfected with Flag-hBeclin-1, FlaghBeclin-1(DBcl-2BD) or hBeclin-1(DBcl-2BD)-GFP (generously provided by Beth Levine, University of Texas Southwestern Medical Center at Dallas) or mouse Beclin-1-GFP (generously provided by Zhenyu Yue, Mount Sinai School of Medicine, New York) fusion constructs alone or in combination with plasmids encoding wild-type Bcl-2 (wt-Bcl-2) or Bcl-2 variants targeted at their C-termini to the mitochondrial outer membrane (mit-Bcl-2) or the ER membrane (ER-Bcl-2) (Hacki et al, 2000;Kaufmann et al, 2003) (generously provided by Christoph Borner, IMMCR, Albert-Ludwigs-Universita¨t, Freiburg). For immunocytochemistry, immunoprecipitation, immunoblot and caspase assays, cells were cotransfected so that they expressed 0.8-or 1.7-fold molar ratios of Beclin-1 to Bcl-2.…”
Section: Transfectionmentioning
confidence: 99%
“…11,12 Third, bcl-2 family members, including bcl-2 itself, Bax and Bak, as well as the BH3-only protein BIK, localize not only to mitochondria but also to the ER. [13][14][15] Therefore, multiple pathways exist by which the ER can contribute to pro-or antiapoptotic stimuli.…”
Section: Introductionmentioning
confidence: 99%